Siren's fury - Weber, Mary (Storm siren trilogy, 2015)
Summary: Nym has saved Faelen only to discover that Draewulf stole everything she valued. Now he's destroyed her Elemental storm-summoning ability as well. When Nym sneaks off with a host of delegates to Bron, Lord Myles offers her the chance for a new kind of power and the whispered hope that it may do more than simply defeat the monster she loathes. But the secrets the Bron people have kept concealed, along with the horrors Draewulf has developed, may require more than simply harnessing a darker ability. They may require who she is.